Enhancing User Empowerment and Agency through Co-Creation of a Nonattachment-Based Post-Traumatic Stress Reduction Intervention - Tremblay, Lindsay; Van Gordon, William; Elander, James (European Journal of Mental Health, 2025)
Introduction: Individuals with post-traumatic stress typically experience feelings of helplessness, which are often exacerbated by current treatment approaches whereby clinicians tend to rely more on personal experiences than case-by-case, evidence-based care. Aims: This study aimed to address this issue by extending the framework of existing public healthcare interventions to co-create a new nonattachmentbased approach in collaboration with end users and clinicians. The practice of nonattachment involves intentionally releasing judgement of or attachment to events, relationships, and the self, while accepting life’s changes with openness and compassion. Methods: This study employed a three-stage co-creation process: 1) evidence review and stakeholder engagement, 2) co-creation of an initial intervention, and 3) prototyping. Twenty participants (17 with experience of post-traumatic stress and three clinicians) contributed to the intervention’s development over the three stages through one-to-one meetings and group discussions, which were recorded and analyzed using reflexive thematic analysis. Artificial intelligence was used to generate language featured in the final intervention. Results: Key themes identified through the thematic analysis were empowerment and agency, the importance of grounding, as well as normalization and validation. Co-creation input from participants focused primarily on the structure and format of the intervention, while input from clinicians focused on feasibility, barriers to adoption, and safety planning. The final intervention took the form of an online program comprised of 8 self-guided modules integrating nonattachment and mindfulness principles, allowing users to control how and when they interact with the content. Conclusions: To our knowledge, this co-created protocol is the first intervention for post-traumatic stress to be principally grounded in ancient Eastern nonattachment principles. Future studies can now evaluate the intervention to determine its feasibility in post-traumatic stress settings.